Existential Hope and Existential Despair in Ai Apocalypticism and Transhumanism - Singler, Beth (Zygon, 2019)
Drawing on observations from on- and offline fieldwork among transhumanists and artificial superintelligence/singularity-focused groups, this article will explore an anthropology of anxiety around the hoped for, or feared, posthuman future. It will lay out some of the varieties of existential hope and existential despair found in these discussions about predicted events such as the "end of the world" and place them within an anthropological theoretical framework. Two examples will be considered. First, the optimism observed at a transhumanist event will be examined to emphasize the positive affective aspects of certain apocalypse scenarios, especially those with an implicit eschatological direction. Second, an online location where examples of existential despair can be noted will be explored further to demonstrate the kinds of negative responses to certain superintelligence/singularity ideas. These examples of existential hope and despair will demonstrate the intrinsic role of anxiety in ideas about a future artificial intelligence apocalypse.